Genome-Wide Analysis Suggests the Relaxed Purifying Selection Affect the Evolution of WOX Genes in Pyrus bretschneideri, Prunus persica, Prunus mume, and Fragaria vesca - Cao, Yunpeng; Han, Yahui; Meng, Dandan; Li, Guohui; Li, Dahui; Abdullah, Muhammad; Jin, Qing; Lin, Yi; Cai, Yongping (Frontiers in Genetics, 2017)
WUSCHEL-related homeobox (WOX) family is one of the largest group of transcription factors (TFs) specifically found in plant kingdom. WOX TFs play an important role in plant development processes and evolutionary novelties. Although the roles of WOXs in Arabidopsis and rice have been well-studied, however, little are known about the relationships among the main clades in the molecular evolution of these genes in Rosaceae. Here, we carried out a genome-wide analysis and identified 14, 10, 10, and 9 of WOX genes from four Rosaceae species (Fragaria vesca, Prunus persica, Prunus mume, and Pyrus bretschneideri, respectively). According to evolutionary analysis, as well as amino acid sequences of their homodomains, these genes were divided into three clades with nine subgroups. Furthermore, due to the conserved structural patterns among these WOX genes, it was proposed that there should exist some highly conserved regions of microsynteny in the four Rosaceae species. Moreover, most of WOX gene pairs were presented with the conserved orientation among syntenic genome regions. In addition, according to substitution models analysis using PMAL software, no significant positive selection was detected, but type I functional divergence was identified among certain amino acids in WOX protein. These results revealed that the relaxed purifying selection might be the main driving force during the evolution of WOX genes in the tested Rosaceae species. Our result will be useful for further precise research on evolution of the WOX genes in family Rosaceae.